Giant symptomatic hydatid cyst requiring pneumonectomy: Pneumonektomija zaradi velike simptomatske hidatidne ciste - Crnjac, Anton; Hojski, Aljaž; Greif, Boris; Petek, Tadej; Vidovič, Damjan (Acta Medico-Biotechnica, 2021)
Purpose: This paper discusses the diagnostic approach, treatment and certain complications in the treatment of patients with hydatid lung disease. The objective of surgical treatment is removal of the cyst and preservation of the healthy lung parenchyma. In cases of overgrowth of the pulmonary artery, which are rare, it is sometimes necessary to remove the lung;this is linked with the possibility of serious postoperative complications.Case report: We present the case of a 27–year–old patient with a hydatid cyst overgrowing the pulmonary artery and requiring removal of the left lung. After the surgery, acute respiratory distress syndrome (ARDS) developed in the remaining right lung. Extracorporeal membrane oxidation (ECMO) was required. Despite a serious complication of the extensive surgical resection, the patient left the hospital after four weeks without major health problems.Conclusion: In patients with giant pulmonary hydatidcysts it is possible to perform surgery, preserve the lung and continue treatment with the addition of albendazole therapy. The removal of the lung, on account of overgrowth of the pulmonary artery, can significantly affect the course of postoperative treatment. When planning the surgical procedure, a precise image of the pulmonary hilar structures is essential.
Keywords: hydatid cyst; albendazole; diagnostic radiology; surgical treatment; perioperative complications